Effect of vestibular deepening on the periodontal status of teeth – preliminary study - Wyrębek, Beata; Górska, Renata; Nędzi-Góra, Małgorzata; Plakwicz, Paweł (Journal of Stomatology, 2016)
Aim of the study. To assess if vestibular deepening improves periodontal parameters of mandibular anterior teeth with gingival recessions. Materials and methods. Ten anterior mandibular teeth in ten patients aged 20 to 49 years with gingival recessions and gingivitis at the mandibular incisors, shallow vestibule and pull-syndrome were examined. Vestibular deepening was performed with modified Kazanjian vestibuloplasty. Probing pocket depth (PPD), clinical attachment level (CAL), gingival recessions (GR), keratinized gingiva (KG), depth of vestibule (VOD), presence of plaque and bleeding were assessed for 98 teeth in total at baseline and at three and twelve months after surgery. Results. Three and twelve months after surgery there was a statistically significant improvement in PPD, CAL and GR when compared to baseline. Mean PPD, CAL and GR were lower (0.3 mm, 1.0 mm and 0.7 mm, respectively) at labial surface of central incisors, and KG significantly increased at labial surface of central and lateral incisors (0.8 mm and 0.6 mm, respectively). The vestibule was deeper at central and lateral incisors, canines and first premolars (3.8 mm, 3.3 mm, 2.3 mm and 0.5 mm, respectively) and the presence of bleeding and plaque was reduced at all assessed teeth. Conclusions. Vestibuloplasty positively changed periodontal parameters at incisors with gingival recessions and did not adversely affect teeth that did not present recessions at the baseline. This type of treatment could be an attractive alternative in patients presenting Class III and IV recessions in cases when tissue grafting is not possible and less predictable.